Crystal structure of human GDF11. Issue 3 (2nd March 2016) - Padyana, Anil K.; Vaidialingam, Bhamini; Hayes, David B.; Gupta, Priyanka; Franti, Michael; Farrow, Neil A.
Abstract : The structure of human growth differentiation factor 11 (GDF11) determined to a resolution of 1.50 Å reveals subtle conformational differences when compared with the previously determined structure of human myostatin (GDF8) while maintaining a highly similar quaternary architecture. Abstract : Members of the TGF‐β family of proteins are believed to play critical roles in cellular signaling processes such as those involved in muscle differentiation. The extent to which individual family members have been characterized and linked to biological function varies greatly. The role of myostatin, also known as growth differentiation factor 8 (GDF8), as an inhibitor of muscle differentiation is well understood through genetic linkages. In contrast, the role of growth differentiation factor 11 (GDF11) is much less well understood. In humans, the mature forms of GDF11 and myostatin are over 94% identical. In order to understand the role that the small differences in sequence may play in the differential signaling of these molecules, the crystal structure of GDF11 was determined to a resolution of 1.50 Å. A comparison of the GDF11 structure with those of other family members reveals that the canonical TGF‐β domain fold is conserved. A detailed structural comparison of GDF11 and myostatin shows that several of the differences between these proteins are likely to be localized at interfaces that are critical for the interaction with downstream receptors and inhibitors.